Sufficiency range for cotton cropped in Brazil midwest: I. Macronutrients - Camacho, Marcos Antonio; Natale, William [UNESP]; Barbosa, José Carlos [UNESP] (FapUNIFESP (SciELO), 2012)
The cotton growth occupies about 1.1 million hectares in Brazil and the midwest, especially the state of Mato Grosso, is the largest producer in the country. This work aimed to establish the sufficiency ranges for macronutrients in cotton crops by the method of mathematical chance. The work was carried out from 2000 to 2003 in the cities of Costa Rica (MS), Diamantino and Sapezal (MT), totaling 152 samples of plant tissue and yield. The chance mathematics method was adequate for to establish cotton macronutrients references values, can be to help parameters were the conventional research cannot to prove in the small time space. The use of different yields for the calculation of mathematical chance (4,000 and 4,500kg ha-1) in the population studied, no difference between the sufficiency ranges for macronutrients. The macronutrients sufficiency range was, in the mg kg-1, 33-45; 3,8-5,3; 15-21; 20-36; 4,0-7,2 e 2,8-8,6 for N, P, K, Ca, Mg e S, respectly. The indicated range, however to similar with the recommendations published, they demonstrate improvement about to obtainment of increases productivities.
Faixas de suficiência para a cultura do algodão no centro-oeste do Brasil: I. Macronutrientes
Keywords: Gossypium hirsutum r. latifolium; Leave diagnosis; Nutritional available; Sufficiency range